PERLINDUNGAN HUKUM TERHADAP HAK PEKERJA YANG DIPUTUS HUBUNGAN KERJANYA KARENA PEKERJA MENOLAK MUTASI PADA PT SANGGRAHA DHIKA (STUDI KASUS PUTUSAN NOMOR 210/PDT.SUS-PHI/2016/PN.JKT.PST) - Sella Haryanto; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2018)
Employees hold an importat role in a company. The importance of employees can be found in Article 32 of Indonesian’s Labor Law 2003. Article 32 stated that an employee’s mutation must be protected by the law and be subjected to their capabilities and abilities. Therefore the rights of employees are protected by the law. In reality it is difficult to implement the regulation that has been made. Employees mutation without concerning on their capabilities and abilties often happen. This often leds to the termination of contract between the parties involved which results in unfulfilled employee’s rights by the company. Related to the verdict of Central Jakarta Industrial Relations Court number 210/Pdt.sus-Phi/2016/Pn.Jkt.Pst the employee as the plaintiff was mutated to a ifferent field of work which is not his ability but instead the court’s verdict inflicted a financial loss to the plaintiff as the plaintiff didn’t obtain his rights in accordance of Article 156 of Indonesian’s Labor Law 2003.